EP 17. High-resolution ultrasound of the vagus nerve in healthy subjects. Issue 9 (September 2016) - Pelz, J.; Henn, P.; Saur, D.; Classen, J.; Weise, D.
Abstract : Background: Over the last decade, examination of peripheral nerves with high-resolution ultrasound (HRUS) has been established as a useful diagnostic tool and now routinely complements electrophysiological studies in various diseases. Prerequisite for nerve HRUS are well-defined reference values. Notably, reference values for most cranial nerves and in particular the vagus nerve (VN) are variable (Cartwright et al., 2008; López-Hernández and García-Escrivá, 2014 ) and, overall, scarcely reported. Aim of this study was to assess age-related reference values for the VN and to examine interrater reliability. Herewith, we report preliminary results of the first training cohort. Methods: Both VNs of 10 healthy subjects (6 female, median age 29 years) without history of cardiac disease, especially arrhythmia, were examined with HRUS using a 15 MHz ultrasound transducer (Esaote MyLab Five, probe LA435). Cross-sectional area (CSA) of each VN was assessed at 2 points: at the level of the distal common carotid artery before beginning of the bulb (proximal reading point) and at the level of the thyroid gland (distal reading point). Three ultrasound images at each reading point were recorded with subsequent assessment of CSA. Each subject was examined by 2 sonographers experienced in peripheral nerve ultrasound. Three-factorial (2 × 2 × 2) repeated measures ANOVA (ANOVArm) were performed with the factors GROUP (examiner 1, examiner 2), LEVEL (proximal, distal) and SIDE (right, left). Results: Median CSA differed between the right and the left VN. This finding was supported by a significant ANOVArm that only revealed a significant main effect of SIDE ( F  = 14.630, p  = 0.005). Median CSA of the VN at the proximal level was larger on the right (examiner 1/examiner 2: 2.8 ± 0.5 mm 2 [mean ± SD]/2.6 ± 0.5 mm 2 ) in comparison to the left side (2.3 ± 0.4 mm 2 /2.1 ± 0.4 mm 2 ; p  = 0.023 and p  = 0.063, respectively; student t-test). At the distal level, median CSA of the right VN was also larger (2.7 ± 0.5 mm 2 /2.5 ± 0.6 mm 2 ) than of the left VN (2.2 ± 0.5 mm 2 /1.9 ± 0.4 mm 2 ; p  = 0.021 and p  = 0.012, respectively). Interrater reliability (intraclass correlation coefficient [ICC]) was moderate for the proximal (ICC 0.69, 95% confidence interval: 0.18–0.88) as well as for the distal (ICC 0.78, 95% confidence interval: 0.45–0.91) reading point. Sonographic assessment of the VN was found to be performed more easily at the level of the thyroid gland. Pulsating common carotid artery and the internal jugular vein in direct vicinity to VN represented significant technical problems interfering with VN sonography, Conclusion: These preliminary findings point to a larger CSA of the right VN compared to the left VN, which emphasises the need for side-specific reference values. Interrater reliability was moderate for even experienced sonographers and may have to be improved by dedicated training.